2021
DOI: 10.3390/sym13020164
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon Structure and Spin Effects in Elastic Hadron Scattering

Abstract: Soft diffraction phenomena in elastic nucleon scattering are considered from the viewpoint of the spin dependence of the interaction potential. Spin-dependent pomeron effects are analyzed for elastic pp scattering, and spin-dependent differential cross sections and spin correlation parameters are calculated. The spin correlation parameter AN is examined on the basis of experimental data from s=4.9 GeV up to 23.4GeV in the framework of the extended High Energy Generalized Structure (HEGS) model. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in spin physics have led to a proposal of using storage rings for the search of axion-like particles, which are one of the candidates for explaining the dark matter in the Universe. The details of spin degrees role, its studies and perspectivesstudies of these can be found in [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Reference [4] also discusses soft diffraction phenomena in elastic pp scattering. It discusses the Coulomb-Nucleon phase factor and dependencies of differential cross-section of elastic pp-scattering on t at small values of t and in the region of diffraction minimum.…”
Section: Contributionsmentioning
confidence: 99%
“…The measurements performed by STAR Collaboration [5] demonstrate that, in the range √ −t < 0.2 GeV, the spin-flip events take place due to electromagnetic interaction only. In their turn, available data on the proton-proton EDS at lower energies [6][7][8] point to the fact that, in the interval 0.5 GeV < √ −t < 1.5 GeV, the spin-flip contributions affect the differential cross-section very slightly, and, thus, they could be considered negligible, in the leading approximation (detailed discussion of this matter can be found in a recent paper [9]). Therefore, in further, we assume their subdominance in the whole kinematic range relevant for the high-energy EDS of nucleons.…”
Section: Helicity Currents Of Protonsmentioning
confidence: 99%
“…The dashed lines are related to the one-Reggeon eikonal approximation wherein the FR exchange contribution to the eikonal is ignored Fig. 9 The differential cross-sections of the p p and p p EDS at the ISR energies in the CNI region able underestimation of the proton-proton EDS differential cross-sections at √ s < 63 GeV and √ −t > 1.3 GeV (see Fig. 3) can be related (at least, in part) to spin-flip effects.…”
Section: Other Sources Of Divergences Between the Model Curves And The Experimental Datamentioning
confidence: 99%
“…It allows one to find some new features in the differential cross section of pp-scattering in the unique experimental data of the TOTEM collaboration at √ s = 13 TeV (small oscillations [28] and anomalous behavior at small momentum transfer [29] ). The inclusion of the spin-flip parts of the scattering amplitude allows one to describe the low energy experimental polarization data of the pp elastic scattering [30], which are shown in the corresponding figures in [29].…”
Section: Hadron Form Factors and Elastic Nucleon-nucleon Scatteringmentioning
confidence: 99%